UZBEKISTAN’S AGRICULTURAL REFORMS TO INCREASE EXPORT POTENTIAL - Sayyora Khalmirzayeva (Modern American Journals, 2025)
This article underscores the persistent and sustained initiatives undertaken by the government of the Republic of Uzbekistan to augment the export of agricultural products. Positioned as the primary architects of policies, state organizations play an exclusive role in formulating strategies that not only analyze global trends but also consider market dynamics. This comprehensive approach is geared toward adapting and implementing both new and existing policy reforms in the agricultural market and production sector. The emphasis on continuous analysis of market dynamics reflects a commitment to staying abreast of changes in global demand, supply, and trade patterns. This ongoing assessment enables timely adjustments to policies, ensuring they remain responsive to the evolving landscape of the international agricultural market. The article suggests that the Republic of Uzbekistan recognizes the pivotal role of the agricultural sector in its economic growth and is actively working through its state organizations to position itself strategically in the global market. By adopting adaptive policies and reforms, the government aims to enhance the competitiveness of its agricultural products and foster sustained growth in agricultural exports.
Keywords: Agriculture, policy reforms, import of products, export of agricultural products, Uzbekistan, market share, global trends, state policy, income growth, agricultural economics, strategy for development, legislative acts, competition, regional expansion.